QTL Mapping of Adult-Plant Resistance to Leaf Rust in the Wheat Cross Zhou 8425B/Chinese Spring Using High-Density SNP Markers - Zhang, Peipei; Yin, Guihong; Zhou, Yue; Qi, Aiyong; Gao, Fengmei; Xia, Xianchun; He, Zhonghu; Li, Zaifeng; Liu, Daqun (Frontiers in Plant Science, 2017)
Leaf rust is a destructive foliar disease of common wheat (Triticum aestivum L.) worldwide. Growing resistant cultivars with adult plant resistance (APR) is an effective means to control the disease. In the present study, 244 recombinant inbred lines (RILs) from the Zhou 8425B/Chinese Spring cross were phenotyped for leaf rust severities during the 2011-2012, 2012-2013, 2013-2014 and 2014-2015 cropping seasons at Baoding, Hebei province, and 2012-2013 and 2013-2014 cropping seasons in Zhoukou, Henan province. The population was genotyped using the high-density Illumina iSelect 90K SNP assay and SSR markers. Inclusive composite interval mapping identified eight QTL, designated as QLr.hebau-2AL, QLr.hebau-2BS, QLr.hebau-3A, QLr.hebau-3BS, QLr.hebau-4AL, QLr.hebau-4B, QLr.hebau-5BL and QLr.hebau-7DS, respectively. QLr.hebau-2BS, QLr.hebau-3A, QLr.hebau-3BS and QLr.hebau-5BL were derived from Zhou 8425B, whereas the other four were from Chinese Spring. Three stable QTL on chromosomes 2BS, 4B and 7DS explained 7.5-10.6%, 5.5-24.4% and 11.2-20.9% of the phenotypic variance, respectively. QLr.hebau-2BS in Zhou 8425B might be the same as LrZH22 in Zhoumai 22; QLr.hebau-4B might be the residual resistance of Lr12, and QLr.hebau-7DS is Lr34. QLr.hebau-2AL, QLr.hebau-3BS, QLr.hebau-4AL and QLr.hebau-5BL are likely to be new APR QTL. These QTL and closely linked SNP markers can be used for fine mapping, candidate gene discovery, and marker-assisted selection in wheat breeding.